2017
DOI: 10.12659/msm.907600
|View full text |Cite
|
Sign up to set email alerts
|

Up-Regulated Maternal Embryonic Leucine Zipper Kinase Predicts Poor Prognosis of Hepatocellular Carcinoma Patients in a Chinese Han Population

Abstract: BackgroundMaternal embryonic leucine zipper kinase (MELK) has been implicated in various types of tumors, but its expression profile and clinicopathologic significance in hepatocellular carcinoma (HCC) in Chinese Han people remains unknown. Therefore, this study attempted to investigate the expression pattern of MELK in HCC tissues obtained from a Chinese Han population.Material/MethodsThe expression of MELK, from RNA to protein levels, in HCC or disease-free human liver tissues was evaluated using quantitativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 22 publications
2
11
0
Order By: Relevance
“…Overexpression of MELK was also associated with distant metastasis, lymph node involvement and poor prognosis in GC patients (17). In HCC, high MELK protein expression was not only related with short disease-free survival and overall survival but also correlated with vascular invasion and higher pathological tumor-nodule-metastasis stage (16). Consistently, we observed that the expression of MELK was much higher in metastatic ESCC tissues, compared to that from primary tumors.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Overexpression of MELK was also associated with distant metastasis, lymph node involvement and poor prognosis in GC patients (17). In HCC, high MELK protein expression was not only related with short disease-free survival and overall survival but also correlated with vascular invasion and higher pathological tumor-nodule-metastasis stage (16). Consistently, we observed that the expression of MELK was much higher in metastatic ESCC tissues, compared to that from primary tumors.…”
Section: Discussionsupporting
confidence: 79%
“…Furthermore, elevated MELK protein expression was correlated with decreased overall survival and disease-free survival in various types of human cancer (9,(17)(18)(19). Notably, it revealed that high MELK protein expression was also significantly associated with higher pathological tumor-nodule-metastasis stage, vascular invasion (16). Moreover, the abnormal expression of MELK was related to cervical cancer metastasis at early stage (9).…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Over expression of MELK is associated with a poor prognosis in several malignancies . In breast and gastric cancers, the expression of MELK correlated with the metastasis and recurrence of tumors.…”
Section: Discussionmentioning
confidence: 99%
“…MELK has been reported to participate in tumour progression via the JNK, p53, Bcl-G and forkhead box protein M1 (FOXM1) signalling pathways, which are all extremely important in multiple human cancer types (8,(25)(26)(27)(28). Gu et al (28) indicated that MELK regulates glioma cell growth via the JNK/p53 pathway.…”
Section: Discussionmentioning
confidence: 99%